Survivin-targeting Artificial MicroRNAs Mediated by Adenovirus Suppress Tumor Activity in Cancer Cells and Xenograft Models - Yudan Chi; Xiang Wang; Yong Yang; Chao Zhang; Hildegund C J Ertl; Dongming Zhou (Elsevier, 2014)
Survivin is highly expressed in most human tumors and fetal tissue, and absent in terminally differentiated cells. It promotes tumor cell proliferation by negatively regulating cell apoptosis and facilitating cell division. Survivin's selective expression pattern suggests that it might be a suitable target for cancer therapy, which would promote death of transformed but not normal cells. This was tested using artificial microRNAs (amiRNAs) targeting survivin. After screening, two effective amiRNAs, which knocked down survivin expression, were identified and cloned into a replication-defective adenoviral vector. Tumor cells infected with the recombinant vector downregulated expression of survivin and underwent apoptotic cell death. Further studies showed that apoptosis was associated with increases in caspase 3 and cleaved Poly (ADP-ribose) polymerase, and activation of the p53 signaling pathway. Furthermore, amiRNA treatment caused blockade of mitosis and cell cycle arrest at the G2/M phase. In vivo, survivin-targeting amiRNAs expressed by adenoviral vectors effectively delayed growth of hepatocellular and cervical carcinomas in mouse xenograft models. These results indicate that silencing of survivin by amiRNA has potential for treatment of cancer.